2016
DOI: 10.1088/0965-0393/24/3/035007
|View full text |Cite
|
Sign up to set email alerts
|

Minimum energy path for the nucleation of misfit dislocations in Ge/Si(0 0 1) heteroepitaxy

Abstract: A possible mechanism for the formation of a 90 • misfit dislocation at the Ge/Si(001) interface through homogeneous nucleation is identified from atomic scale calculations where a minimum energy path connecting the coherent epitaxial state and a final state with a 90 • misfit dislocation is found using the nudged elastic band method. The initial path is generated using a repulsive bias activation procedure in a model system including 75000 atoms. The energy along the path exhibits two maxima in the energy. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The presence of a step on the film can significantly lower the activation energy for the nucleation of a MD. The presence of a step indeed increases the volume of the region for which some strain is released by the nucleation of a dislocation, it can also act as a stress concentrator 19 and finally, the step may be removed by the nucleation of dislocation 17 . Preliminary calculations indicate that the activation energy for the nucleation of a 60° MD can be lowered to 2 eV by the presence of a double D B step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a step on the film can significantly lower the activation energy for the nucleation of a MD. The presence of a step indeed increases the volume of the region for which some strain is released by the nucleation of a dislocation, it can also act as a stress concentrator 19 and finally, the step may be removed by the nucleation of dislocation 17 . Preliminary calculations indicate that the activation energy for the nucleation of a 60° MD can be lowered to 2 eV by the presence of a double D B step.…”
Section: Resultsmentioning
confidence: 99%
“…Previous atomistic simulation studies have predicted activation energies larger than 10 eV for the nucleation of MDs in Ge/Si 16 , 17 . Such a high barrier cannot be overcome by thermal fluctuation on a short time scale even at a temperature close to the melting temperature.…”
Section: Introductionmentioning
confidence: 94%
“…The mechanisms for the formation of 90 • MDs previously presented in the literature require as a first step the formation of a 60 • MD [17] which is usually assumed to occur through the half loop nucleation process. In a previous study of the same system and using the Stillinger-Weber potential, it was shown that the half loop nucleation of a 60 • MD has an activation energy of 54 eV [20].…”
Section: Discussionmentioning
confidence: 97%
“…The coherent Ge film is 19 layers thick with a p(2 × 1) dimer reconstruction of the surface. This film thickness corresponds to the critical thickness for the formation of a 60 • MD [20].…”
Section: Model Systemmentioning
confidence: 99%
See 1 more Smart Citation